Does Demolition Lead to a Reduction in Nearby Crime Associated With Abandoned Properties?. Issue 2 (4th March 2023) - Han, Hye-Sung; Helm, Scott
Abstract: Scholars argue that housing abandonment increases area criminal activity. The link between abandoned properties and crime has led to the assumption that demolition of abandoned properties will stymie criminal activity and thus improve neighborhood safety. Although cities spend millions of federal and local funds on demolitions every year, very little research has explored the empirical effects of demolitions on crime. Does demolition lead to a reduction in nearby crime? This study answers this question by quantifying the relationship between abandoned building demolition programs and nearby crime using a difference-in-difference approach on 559 abandoned buildings demolished in Kansas City, Missouri, between 2012 and 2016. This study finds that demolition of abandoned properties does not have any significant impact on nearby violent and property crime. This analysis shows that a change in nearby crime is attributable to differences in nearby socioeconomic and housing characteristics, rather than to the demolition of abandoned properties.